Introduction to electronic control engineering - Siemens ([S.l.] : New Age International Pvt. Ltd., 2010)
This Handbook, based on a German edition, has been compiled by specialists from many branches of engineering to meet the practical everyday needs of the electrical engineer. It contains a wealth of formulae, graphs and tables presented in a clear and concise manner. Ample explanations of theoretical relationships and numerous definitions are included.